Standardization of Pre-sowing Seed Treatments with Selected Biofertilizers on Seedling Parameters of Wheat (Triticum aestivum L.) - DEEPENDRA MAHALAL; VAIDURYA PRATAP SAHI; SHIVAM KUMAR RAI; PRASHANT KUMAR RAI (Seed Research, 2026)
This study was undertaken to investigate the effects of various microbial seed treatments on germination, seedling growth, and nutritional content in wheat plants. Results indicated that Mycorrhiza treatments, @10%, significantly improved seed germination, seedling length, shoot length, root length, and protein content compared to the untreated control whereas Azotobacter treatments exhibited only marginal enhancements in germination percentage and protein content. Conversely, Trichoderma treatments showed slight reductions in germination percentage and seedling growth parameters. Rhizobium treatments exhibited mixed effects on germination percentage and seedling growth. Notably, Mycorrhiza treatments showed consistent positive effects on multiple parameters, highlighting their potential as seed treatment for enhancing crop performance and nutritional quality. These findings underscore the importance of selecting appropriate microbial treatments tailored to specific crop requirements for sustainable agricultural practices. Top of Form